THE DEVELOPMENT OF SPEAKING SKILLS IN PRIMARY SCHOOL STUDENTS - Axmadjonova Madina Maxmudjon qizi; Vaisboyeva Barno Vaisboyevna (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
The development of speaking skills in primary school student is essential for their overall communication competence and academic success. This study explores various strategies to enhance speaking abilities among young learners, emphasizing interactive learning environments, group discussions, and storytelling techniques. The findings suggest that teacher modeling and peer feedback foster a supportive atmosphere for language practice. Additionally, the use of multimedia resources and games engages students actively. By implementing these methods, educators can significantly improve students' confidence and proficiency in speaking. Furthermore, the integration of diverse cultural narratives in storytelling not only enriches language exposure but also promotes inclusivity among students. Ultimately, fostering speaking skills at an early age lays a strong foundation for lifelong communication abilities, preparing students for future academic and social challenges.